Association between functional gastrointestinal disorders and migraine in children and adolescents: a case-control study. (October 2016) - Le Gal, Julie; Michel, Jean-Francois; Rinaldi, Victoria Elisa; Spiri, Daniele; Moretti, Raffaella; Bettati, Donatella; Romanello, Silvia; Berlese, Paola; Lualdi, Rosa; Boizeau, Priscilla; Viala, Jerome; Bellaiche, Marc; et al.
Summary: Background: Functional gastrointestinal disorders and migraine are both common causes of medical attention. We have previously shown an association between migraine and infant colic. In this case-control study, we aimed to establish whether there is an association between migraine and other functional gastrointestinal disorders in children and adolescents. Methods: We included children and adolescents aged 6–17 years presenting to the emergency department of four tertiary hospitals in France and Italy. Patients diagnosed with either migraine or tension-type headache by the hospital's paediatric neurologist were enrolled as cases. Patients presenting to the emergency department with minor trauma and no history of recurrent headache were enrolled as controls. Investigators masked to a patient's group allocation diagnosed functional gastrointestinal disorders using the Rome III diagnostic criteria. Univariable and multivariable analyses were done to identify specific disorders and baseline factors associated with migraines and tension-type headache. Findings: Between Nov 1, 2014, and Jan 31, 2015, we enrolled 648 controls and 424 cases (257 patients with migraine and 167 with tension-type headache). 83 (32%) children and adolescents in the migraine group were diagnosed with functional gastrointestinal disorders compared with 118 (18%) in the control group (p<0·0001). Multivariable logistic regression showed a significant association between migraine and three gastrointestinal disorders: functional dyspepsia (odds ratio 10·76, 95% CI 3·52–32·85; p<0·0001), irritable bowel syndrome (3·47, 1·81–6·62; p=0·0002), and abdominal migraine (5·87, 1·95–17·69; p=0·002). By contrast, there was an inverse association between migraine and functional constipation (0·34, 0·14–0·84, p=0·02). 41 (25%) participants with tension-type headache had functional gastrointestinal disorders, which did not significantly differ from the prevalence of these disorders in the control group (p=0·07); no significant association was noted between any functional gastrointestinal disease and tension-type headaches. Interpretation: Three abdominal-pain-related functional gastrointestinal disorders were associated with migraine in children and adolescents. These findings are of value to the diagnosis and management of these common diseases. Future studies should investigate whether antimigraine drugs are of benefit in functional gastrointestinal disorders. Funding: None.